Tinjauan Sistematis tentang Faktor Penyebab dan Intervensi: Prokrastinasi Akademik Ditinjau dari Pastoral Konseling - Indyah Novi Styorini; Kadek Suranata; I Ketut Dharsana (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
Academic procrastination remains a significant barrier to student success, affecting both academic performance and mental health. This systematic review discusses the core factors contributing to academic procrastination, including fear of failure, perfectionism, and difficulties in emotion regulation, which cause students to delay academic tasks. The study uses the PRISMA methodology, synthesizing findings from 37 empirical studies published between 2014 and 2025 to evaluate the effectiveness of interventions. Cognitive-behavioral therapy (CBT) and motivational strategies have emerged as effective approaches in reducing procrastination by addressing unrealistic thinking patterns and enhancing self-regulation skills. In addition, technology-assisted interventions, such as digital planning tools, have shown potential in supporting students' time management. From the perspective of Christian Religious Education, pastoral counseling approaches also provide important contributions through the integration of psychological and spiritual aspects, which help students build meaning, enhance emotional regulation, and strengthen intrinsic motivation in completing academic tasks.